2020
DOI: 10.3390/electronics9020266
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Enhanced Framework for Performance Evaluation of a Recommending Interface with Varied Recommendation Position and Intensity Based on Eye-Tracking Equipment Data Processing

Abstract: The increasing amount of marketing content in e-commerce websites results in the limited attention of users. For recommender systems, the way recommended items are presented becomes as important as the underlying algorithms for product selection. In order to improve the effectiveness of content presentation, marketing experts experiment with the layout and other visual aspects of website elements to find the most suitable solution. This study investigates those aspects for a recommending interface. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments, 15,922 fixation records were generated by eye-tracking devices from 52 participants. The results show that the accuracies of training dataset and testing dataset were 98.4% and 98.2%, respectively [55].…”
Section: Recommendation Systems and Education Systemsmentioning
confidence: 98%
“…They have used K-nearest Neighbour (KNN) as a classification method for this purpose and tested the result on two real datasets of women's clothing and furniture. A recent study [55] provides a user interface for an e-commerce website based on users' behavior using a deep neural network method. Their analysis revealed the effect of a website layout to recommended items based on the user's behavior.…”
Section: Recommendation Systems In E-commercementioning
confidence: 99%
“…Application Reference e-commerce Items recommendations to buyers [4,5] Movie or video recommendations [43] Transportation Path Recommendation for transporting goodOr passengers [8,39,49] Recommendations to Tourists [50][51][52] Venue recommendation [53][54][55] e-health Medical advice or treatment plan recommendation [6,46,63,64] Recommending Personalized services to patients [44] Appointments recommendation to clinicians [45] Health recommendations in mobile systems [59] Healthy behavioral recommendations [61] Diet recommendation [62] Agriculture Fertilizer recommendation to farmers [7] Crops issue recommendation [47] Assisting farmers inquiries [48] Agricultural products recommendation [65] Crop cultivation suggestion [40,[66][67][68] Media Event recommendations [80] Museum recommendations [81,82] Multimedia recommendations [83][84][85] Open Social Networks recommendations [86][87][88][89][90]…”
Section: Areamentioning
confidence: 99%
“…In turn, they can solve recognition, regression, semi-supervised and unsupervised problems [42][43][44]. Deep learning has proven its efficacy in medical imaging like in many other domains such as self-driving cars, natural language and image processing, predictive forecasting, eye tracking systems, object detection in space, finger print localization systems [45][46][47][48][49]. Vgg16 is one of the deep learning models [50] that is a successful feature extractor in multiple domains having lots of image data.…”
Section: Parallel Multi-parametric Feature Embeddingmentioning
confidence: 99%